Strategies for Strengthening Labour-Based Islamic Education Management in the Perspective of the Rejang Lebong District Disnakertrans Strategic Plan - Syamsir, Syamsir; Hamengkubuwono, Hamengkubuwono; Warlizasusi, Jumira; Fathurrochman, Irwan (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2025)
Providing training and provision of human resources in educational institutions is very necessary to build quality output. Strengthening human resources will also strengthen the institution, because having quality human resources is a valuable asset.This study aims to analyse the strategy for strengthening Islamic education management based on employment by referring to the Strategic Plan (Renstra) of the Department of Manpower and Transmigration of Rejang Lebong Regency for 2021-2026. The research adopts a descriptive qualitative approach using document analysis, applying SWOT analysis and the IPO-OI (Input-Process-Output-Outcome-Impact) framework. The findings indicate that regional employment policies hold significant potential to be integrated into the Islamic education system, particularly in strengthening value-based and skill-oriented curricula. Institutional strengths, funding opportunities, and the potential for cross-sectoral collaboration serve as strategic assets for developing Islamic education that is more relevant, contextual, and empowerment-oriented. Conversely, limitations in human resources, infrastructure, and the mismatch between education and labour market demands remain key challenges that must be addressed through digital transformation and inter-institutional synergy. The study concludes that Islamic education must transform into a strategic force, not only producing pious graduates in terms of personal faith and character but also individuals who are productive and capable of contributing meaningfully to regional social and economic development.